Initiating a conceptualization of the professional work of teaching mathematics in kindergarten in terms of discourse - Sæbbe, Per-Einar; Mosvold, Reidar (NOMAD Nordic Studies in Mathematics Education, 2016)
This study investigates a Norwegian kindergarten teacher’s work of teaching mathematics in an everyday activity involving play with LegoTM bricks. Analysis of the kindergarten teacher’s discourse identifies questioning and affirmation as two core components. We suggest that these are core discursive practices in the work of teaching mathematics in kindergarten. In identifying these practices, a theory of thinking as communicating is applied to investigate what makes these discursive acts of teaching mathematical. Further research is called for to continue investigating kindergarten teachers’ discursive practices in teaching and to continue the efforts to conceptualize the work of teaching mathematics in kindergarten in terms of discourse.